ANALYSIS OF METHODS AND DIAGRAMS OF EXPERT INVESTIGATION OF ROAD-TRANSPORT EVENTS IN CASE KEEPING A VEHICLE ON A PEDESTRIAN - Pasichnyk, A. N.; Kuzmenko, A. I.; Firsov, A. D. (Systems and Technologies, 2018)
The intensity of the use of road transport in various sectors of the economy is growing. This leads to an increase in the accident rate of automobile vehicles and road traffic accidents. Hitting a pedestrian is one of the most common types of traffic accidents. Currently, the total number of deaths on highways in the world is about 1.25 million people. So in 2016 in Ukraine 82.4 thousand traffic accidents with victims were registered. According to the World Bank (2014 estimates), the loss of the Ukrainian economy from road traffic injuries annually amounts to about $ 4.5 billion.The complexity of the study of traffic accidents involving a car and a pedestrian is in a wide variety of factors that in real conditions determine the sequence of stages of their passage. Therefore, for the reliable qualification of such situations in the investigation of traffic accidents, the development and improvement of models and methods for studying the mechanism for their implementation is important. When conducting an automotive technical examination, it is necessary to establish the circumstances and the mechanism of the accident. The reliability of expert analysis of the mechanism of a traffic accident is based on its phased study and reconstruction.In the paper was analyzed and systematized the models and patterns of interaction between participants in traffic accidents to determine their parameters and reconstruction taking into account the traffic situation, factors of influence and the position of the elements of the “driver - car - road - environment” system at the time of a dangerous situation.To increase the reliability of the results of automotive technical expertise of road traffic accidents, it is proposed to use an integrated approach using the data of a theoretical study and experimental confirmation of the correctness of the technical parameters of road traffic accidents. In an expert study of a vehicle’s maneuver, it is quite effective to use empirical-statistical models based on experimental tests.